E-Learning Management to Improve Student Learning Independence in The Covid-19 Pandemic Era - Dumiyati Dumiyati; Candra Aeni (FKIP ULM, 2021)
Abstract. The spread of Covid-19 in Indonesian territory is increasing. In preventing covid-19 transmission in the campus environment, learning methods in universities in all zones must be implemented the e-learning for theoretical and practical subjects. However, when it comes to graduation and student competencies that cannot be implemented in e-learning, these activities can be held while maintaining the health and safety of students and lecturers. On the other hand, not all students and lecturers are accustomed to doing e-learning. Therefore, problems will arise about how e-learning management can improve student learning independence in the Economic Education Study Program of Ronggolawe University. This research was descriptive using the survey method. The research subjects were the head of the study program, lecturers, students and support technicians data collection techniques through questionnaires and documentation of e-learning implementation reports. The research data analysis was carried out descriptively by calculating the percentage and through the average score, interval, and categorization. Based on the data analysis, it was obtained: 1) e-learning management was 3.49 (quite effective); 2) Students responded positively to online learning during the Covid-19 pandemic, 3) independent learning in e-learning shows that 7.69% of students have low learning independence, 21.61% are less independent, 40.07% are quite independent and 27.63% have high independence. It could be prepared that e-learning management was quite effective in increasing student learning independence. However, there were still some aspects that need to be improved. It can be concluded that the management of e-learning was quite effective in increasing student learning independence. However, there were still some aspects that needed to be improved. These aspects included: 1) Optimizing the planning and implementation of e-learning, 2) preparing a repository of digital materials that are easily accessible to students, 3) the readiness of students to participate in e-learning.Keywords: Management, E-Learning, Learning Independence